Of Temporal Politics and Demographic Anxieties: "Young Mothers" in Demographic Predictions and Social Life in Vanuatu - Widmer, Alexandra (Anthropologica, 2013)
In this article, I examine demographic predictions and preliminary youth and population policy in concert with young women's experiences during and immediately after pregnancy in Vanuatu, a Pacific island nation with rapid popu lation growth. I propose that time, in representations of the future and the past as they relate to social and biological reproduction, is a valuable lens for analyzing the interplay between demographic knowledge in development discourse and daily lives of young women. In this way, I add the notion of temporal politics to the social and historical analysis of demography that emphasizes biopolitics and geopolitics.